2D+t Wavelet Domain Video Watermarking. (28th March 2012) - Bhowmik, Deepayan; Abhayaratne, Charith
Abstract : A novel watermarking framework for scalable coded video that improves the robustness against quality scalable compression is presented in this paper. Unlike the conventional spatial-domain (t + 2D) water-marking scheme where the motion compensated temporal filtering (MCTF) is performed on the spatial frame-wise video data to decompose the video, the proposed framework applies the MCTF in the wavelet domain (2D + t) to generate the coefficients to embed the watermark. Robustness performances against scalable content adaptation, such as Motion JPEG 2000, MC-EZBC, or H.264-SVC, are reviewed for various combinations of motion compensated 2D + t + 2D using the proposed framework. The MCTF is improved by modifying the update step to follow the motion trajectory in the hierarchical temporal decomposition by using direct motion vector fields in the update step and implied motion vectors in the prediction step. The results show smaller embedding distortion in terms of both peak signal to noise ratio and flickering metrics compared to frame-by-frame video watermarking while the robustness against scalable compression is improved by using 2D + t over the conventional t + 2D domain video watermarking, particularly for blind watermarking schemes where the motion is estimated from the watermarked video.